Modulation of fluid absorption and the secretory response of rat jejunum to cholera toxin by dietary fat. Issue 11 (November 1990) - Sagher, F A; Dodge, J A; Moore, R; McMaster, C; McCaughey, G
Abstract : To study the effects of dietary fat on jejunal water and ion absorption and on cholera toxin-induced secretion, 3 week old Sprague Dawley rats were fed isocaloric diets. Forty per cent of the total calories were given as fat, as butter (high saturated fat), olive oil (high monounsaturated fat), or corn oil (high polyunsaturated fat), with one group on low fat (10% of calories) standard laboratory diet as controls. During in vivo jejunal perfusion studies we found that (i) a polyunsaturated fat (corn oil) supplemented diet improves jejunal absorption of water and electrolytes and these changes are independent of the observed concentrations of luminal prostaglandins; (ii) high dietary fat appreciably reduced the secretory response to cholera toxin, probably without fundamentally changing the mechanism by which cholera toxin induces secretion. We conclude that dietary fat composition altered the permeability and transport characteristics of the small intestine. This observation might have relevance to some human diarrhoeal disorders.